Reliable Euler deconvolution solutions of gravity data throughout the β-VDR and THGED methods: Application to mineral exploration and geological structural mapping - Thanh Pham, Luan; Pomponet Oliveira, Saulo; Le-Huy, Minh; Viet Nguyen, Dat; Quynh Nguyen-Dang, Trang; Duc Do, Than; Van Tran, Kha; Duyen Thi Nguyen, Hong-; Nhu Thi Ngo, To-; Quang Pham, Hung (Vietnam Journal of Earth Sciences, 2024)
Euler deconvolution (ED) is mainly used to estimate the locations and depths of magnetic bodies. This technique can also be applied to gravity anomalies but requires caution, as Euler solutions directly obtained from gravity anomalies may provide misleading results. In addition, the traditional Euler deconvolution generates many spurious solutions and is noise-sensitive. This research presents an improved method for the ED of gravity anomalies. This method is based on a finite-difference method (β-VDR) that provides robust vertical derivatives of gravity anomalies, and the total horizontal gradient-based edge detection method (THGED) used to select the Euler solutions, filtering out spurious solutions. Our method is exemplified with two synthetic gravity models and two real datasets from the Voisey's Bay deposit (Canada) and the Hanoi basin (Vietnam). The advantage of the proposed method is that it can provide the depths more accurately and is less sensitive to noise than some modified ED methods.